2010
DOI: 10.1631/jzus.b0900417
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the 3′ ends of tRNA as the cause of insertion sites of foreign DNA in Prochlorococcus

Abstract: Abstract:The purpose of this study was to investigate the characteristics of transfer RNA (tRNA) responsible for the association between tRNA genes and genes of apparently foreign origin (genomic islands) in five high-light adapted Prochlorococcus strains. Both bidirectional best BLASTP (basic local alignment search tool for proteins) search and the conservation of gene order against each other were utilized to identify genomic islands, and 7 genomic islands were found to be immediately adjacent to tRNAs in Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…S1). tRNA genes are preferred integration sites for mobile elements (Liu & Zhu, 2010;Reiter et al, 1989;Williams, 2002), and as we reported in this study, sequences surrounding these integration sites are often highly conserved (Ou et al, 2006). GIs are also frequently flanked by DRs (Hacker et al, 1997;Ou et al, 2006), and a 22 bp DR flanks the Dnd-GI in ATCC 19977…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…S1). tRNA genes are preferred integration sites for mobile elements (Liu & Zhu, 2010;Reiter et al, 1989;Williams, 2002), and as we reported in this study, sequences surrounding these integration sites are often highly conserved (Ou et al, 2006). GIs are also frequently flanked by DRs (Hacker et al, 1997;Ou et al, 2006), and a 22 bp DR flanks the Dnd-GI in ATCC 19977…”
Section: Discussionsupporting
confidence: 60%
“…3a). Direct repeats (DRs) Dnd genomic island in the M. abscessus complex and tRNA genes are frequently associated with GIs (Hacker et al, 1997;Liu & Zhu, 2010;Ou et al, 2006;Reiter et al, 1989;Williams, 2002). The Dnd-GI insertion site (Fig.…”
Section: Sequence Features At the Dnd-gi Insertion Sitementioning
confidence: 99%
“…Flanking the LGI-T4SS clusters within each of the LGIs are variable genomic regions that indicate multiple insertion, deletion and translocation events, typical of genomic islands and other mobile genetic elements ( Figures S1 and S2 ). The LGIs are all found within hypervariable regions of the genome, adjacent to tRNA genes, which are typical recognition sites for site-specific recombinases such as integrases and transposases [55] , suggesting that these regions are hotspots for the acquisition of horizontally acquired DNA. Indeed there are several direct repeats flanking the LGIs, which correspond to the last 37 to 48 bp at the 3′ end of the tRNA genes adjacent to the LGIs ( Table 1 , Figures S1 and S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A Genomic Island (GI) then is a cluster of genes that is typically between 10-200kb in length and has been transferred horizontally 11 . HGT may contribute to anywhere between 1.6% to 32.6% of the genomes [12][13][14][15][16][17][18][19][20] . This naturally implies that a major factor in the variability across bacterial species and clades can be attributed to GIs 21 .…”
Section: Introductionmentioning
confidence: 99%